(untitled) (International Seven Journal of Multidisciplinary, 2023)
This article is based on a qualitative approach, using a bibliographical and documentary review, and a case study as the research method. It aims to carry out a brief analysis of the application of the Social and Solidarity Economy (SSE) concept in Ecuador. In this way, it addresses the paradigm shift in the concept of development, emphasizing the relevance of other more inclusive and sustainable theoretical approaches, such as "Buen Vivir" and SSE. In addition, this work highlights the constitutional commitment made by the South American country to the "Popular and Solidarity Economy" (EPS) and Buen Vivir, concepts with which it aims to achieve a more just, harmonious and egalitarian society. Finally, actions are proposed for the implementation of the SSE, through specialized education, awareness-raising, gender equality and communication.